2016
DOI: 10.20517/2394-5079.2016.12
|View full text |Cite
|
Sign up to set email alerts
|

Role of natural antioxidants in the therapeutic management of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a growing health problem in humans. HCC is considered the most common of internal malignancy which cause the death of human, but in the developed Western world, HCC is less common accompanied by increasing essentially in incidence, due to it occurs specially in chronic liver disease. HCC associated with various risk factors including hepatitis B virus infection; hepatitis C virus infection; prolonged aflatoxin exposure; and alcoholic cirrhosis. Overall, one-third of cirrhosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 110 publications
(116 reference statements)
0
5
0
Order By: Relevance
“…In the present investigation, GSH and SOD levels were decreased in HCC-induced animals. This depletion may be caused by the increase in free radical generation from metabolism of carcinogenic chemicals used and increased lipid peroxidation as well as decreased expression of these antioxidant enzymes during hepatocellular damage [30]. In garlic and cinnamon oils, HCC-pretreated rats' higher levels of hepatic GSH and SOD noticed may be due to suppression of lipid peroxidation and protein oxidation, inhibition of ROS production consistent with radical scavenging activity, and reduced DNA carcinogen interaction indicating the restoration of the antioxidant system of the liver [31].…”
Section: Discussionmentioning
confidence: 99%
“…In the present investigation, GSH and SOD levels were decreased in HCC-induced animals. This depletion may be caused by the increase in free radical generation from metabolism of carcinogenic chemicals used and increased lipid peroxidation as well as decreased expression of these antioxidant enzymes during hepatocellular damage [30]. In garlic and cinnamon oils, HCC-pretreated rats' higher levels of hepatic GSH and SOD noticed may be due to suppression of lipid peroxidation and protein oxidation, inhibition of ROS production consistent with radical scavenging activity, and reduced DNA carcinogen interaction indicating the restoration of the antioxidant system of the liver [31].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment based on allopathic drugs has been found to be very effective but have been reported to possess severe adverse effects. The medicinal plants or its active compound are rich sources of antioxidants and such antioxidant property of herbs may be involved in the management of diseases including liver diseases [19]. In this regard, olive fruits as a whole and its oil have been confirmed to have a beneficial role in curing disease through its anti-inflammatory, antioxidant and other therapeutic implications including hepatic dysfunctions.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are no proven anti-fibrotic therapeutics, numerous studies are underway to identify new ones and to establish anti-fibrotic activity for popular treatments of liver diseases accompanied by its fibrous degeneration [ 71 ]. Lots of studies have revealed the prophylactic effect of natural antioxidants against HCC [ 72 , 73 ]. However, simple free radical scavengers demonstrated a lack of efficacy, probably because of cell compensatory systems and a complex network of signaling pathways designed to ensure tumor cells’ survival and proliferation.…”
Section: Discussionmentioning
confidence: 99%